The medieval bronze doors of San Zeno, Verona: combining material analyses and art history - M. Mödlinger; J. Bontadi; M. Fellin; M. Fera; M. Negri; J. Utz; G. Ghiara (Heritage Science, 2024)
Abstract The bronze doors of the Basilica of San Zeno in Verona, Italy, are a special case in art history research. They were made by several workshops during the twelfth century: stylistically, two to three workshops were assumed to produce the metal parts of the door. However, it is still unclear when exactly and if this interpretation can be supported by the chemical composition of the metal. In this research we aimed to verify the art history interpretation by identifying the alloy composition of each individual metal plate. The composition of the supporting wooden structures are discussed. A portable ED-XRF instrument and optical microscopes were used to analyse and document the doors non-invasively. The doors were also photographed to produce high resolution orthophotos and 3D models. We can confirm that the metal parts of the doors were made of leaded tin-bronze as well as leaded brass and mounted on a wooden structure mainly made of spruce and oak wood. Chemically, two/three different groups of alloys have been identified, which can be associated with two or three different workshops, and which largely correspond to the stylistic interpretation.